Optimierung von Planetengetriebemotoren - Einfluss des Übersetzungsverhältnisses auf das Kosten-, Gewichts-, Verlust-, Dynamik- und Zuverlässigkeitsverhalten von Planetengetriebemotoren - Kücükyavuz, Ali Kemal

Beitrag zur Reduzierung der Verluste von fluidabdichtenden Wellendichtsystemen - Nolte, Karsten

Verbundprojekt Energieeffiziente Federkraftbremse: Abschlussbericht. Berichtszeitraum: 01.05.2012 - 31.03.2016 - Schadomsky, Magnus Hubert; Zimmer, Detmar; Kriegel, Nils-Peter; Neumann, Christoph; Küter, Winfried; Menzel, Eckard

Reconstruction of three-dimensional turned shaft surfaces with fractal functions - Thielen, Stefan; Magyar, Balázs; Piros, Attila (Tribology International)
A method for the reconstruction of turned shaft surfaces with a (fractal) Weierstrass–Mandelbrot-function (WMF) is presented. The WMF is modified to allow to freely choose a phase-shift for every frequency. The reconstruction is based on distinct profiles in axial and tangential direction and the statistical distribution of low-wavelength portions of the surface is taken into account by adding t-distributed random deviations to the surface. The work is validated by reconstructing measured shaft surfaces with different manufacturing parameters, which shows good accuracy for periodic surfaces. This method allows for a characterization of surfaces with a limited number of parameters and can be used to store the characteristics of measured surfaces with a reduced amount of data compared to a point-cloud surface.
Keywords: Roughness; Structure; Fractal; Machining

Functional investigation of zero lead radial shaft seal counter-surfaces turned with a special method - Thielen, S; Magyar, Balázs; Sauer, B; Schneider, F; Mayer, P; Kirsch, B; Müller, R; v. Harbou, E; Aurich, J.C.

Gekoppelte thermische und tribologische Analyse von Schneckengetrieben - Oehler, M; Magyar, Balázs; Sauer, B

EHD Simulation eines Kettengelenks - Magyar, Balázs; Thielen, S; Löwenstein, M; Becker, A; Sauer, B

Geometrische Genauigkeit von Lasersinter-Bauteilen: Einflüsse und Maßnahmen / Dimensional accuracy of polymer laser sintered parts: Influences and measures
In the polymer laser sinter process, part quality depends on many influencing factors along the process chain. For application of the technology in series production and an integration of laser sintered parts into a technical environment, the dimensional accuracy of parts has to be taken into account. Therefore, occurring deviations of the process have to be known to define tolerances for part design. Dimensional deviations and their scattering have to be reduced and homogenized based on process parameters and build job layout. In this work, the dimensional accuracy of laser sintered parts is analyzed for varied parameter values. Influences of different process and geometrical build job parameters on dimensional deviations are figured out. The experimental results allow an evaluation of more and less important influences. Finally, measures are deduced to reduce and homogenize dimensional deviations.

On design for Additive Manufacturing - evaluating geometrical limitations - dell'Aere, Guido; Zimmer, Detmar (Rapid Prototyping Journal)
Purpose – The purpose of this paper is to present Design Rules for additive manufacturing and a method for their development. Design/methodology/approach – First, a process-independent method for the development of Design Rules was worked out. Therefore, geometrical standard elements and attributes that characterize the elements’ shapes have been defined. Next, the standard elements have been manufactured with different attribute values with Laser Sintering, Laser Melting and Fused Deposition Modeling, and their geometrical quality was examined. From the results, Design Rules for additive manufacturing were derived and summarized in a catalogue. Findings – Due to the process independent method, Design Rules were developed that apply for the different considered additive manufacturing technologies equally. These Design Rules are completely function-independent and easily transferable to individual part designs. Research limitations/implications – The developed Design Rules can only apply for the considered boundary conditions. To extend the Design Rules’ validity, their applicability should be proven for other boundary conditions. Practical implications – The developed Design Rules practically support the design of technical parts. Additionally they can be used for training and teaching in the field of “design for additive manufacturing”. Originality/value – The developed Design Rules constitute a first step toward general Design Rules for Additive Manufacturing. Thus, they might form a suitable basis for further scientific approaches, and the Design Rules can be used to set up teaching documentations for lessons and seminars.

Entwicklung einer Methode zur systematischen Erarbeitung von Maßtoleranzen für additive Fertigungsverfahren - Lieneke, Tobias; Adam, Guido; Leuders, Stefan; Knoop, Frederick; Josupeit, Stefan; Delfs, Patrick; Funke, Nils; Zimmer, Detmar (Proceedings of the Rapid Tech 2015)

Systematical determination of tolerances for additive manufacturing by measuring linear dimensions - Lieneke, Tobias; Adam, Guido; Leuders, Stefan; Knoop, Frederick; Josupeit, Stefan; Delfs, Patrick; Funke, Nils; Zimmer, Detmar (26th Annual International Solid Freeform Fabrication Symposium)
Additive manufacturing offers many technical and economical benefits. In order to profit from these benefits, it is necessary to consider the manufacturing limits and restrictions. This applies in particular to the geometrical accuracy. Therefore, the achievable geometrical accuracy needs to be investigated, which enables the determination of realistic tolerances. Thus, two different aims are considered. The first aim is the determination of dimensional tolerances that can be stated if additive manufacturing is used under normal workshop conditions. Within the second aim, relevant process parameters and manufacturing influences will be optimized in order to reduce dimensional deviations. To achieve both aims a method was developed first. This method identifies relevant influential factors on the geometrical accuracy for the processes Fused Deposition Modeling (FDM), Laser Sintering (LS) and Laser Melting (LM). Factors were selected that are expected to affect the geometrical accuracy mainly. The first investigations deal with measuring linear dimensions on a designed test specimen and the derivation of achievable dimensional tolerances. This paper will present both, the developed method and the first results of the experimental investigations.

Systematische Erarbeitung von Konstruktionsregeln für die additiven Fertigungsverfahren Lasersintern, Laserschmelzen und Fused Deposition Modeling - Adam, Guido

On tolerances for additive manufacturing - Adam, Guido (Inside 3D Printing Conference and Expo)

Entwicklung einer Methode zur systematischen Erarbeitung von Maßtoleranzen für additive Fertigungsverfahren - Lieneke, Tobias (Rapid Tech 2015)

Systematical determination of dimensional tolerances for additive manufacturing - Lieneke, Tobias (26th Annual International Solid Freeform Fabrication Symposium)

Intelligente Betriebsstrategien für Mehrmotorenantriebssysteme - Hölscher, Christian; Strop, Malte; Zimmer, Detmar (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)

Ein Beitrag zur modellbasierten Entwicklung magnetorheologischer Bremsen - Wiehe, Ansgar

Wellendichtsysteme - Zimmer, Detmar; Nolte, Karsten; Hütte, Jürgen

Investigation of wear resistance of dry and cryogenic turned metastable austenitic steel shafts and dry turned and ground carburized steel shafts in the radial shaft seal ring system - Frölich, D.; Magyar, Balázs; Sauer, B.; Mayer, P.; Kirsch, B.; Aurich, J.C.; Skorupski, R.; Smaga, M.; Beck, T.; Eifler, D. (Wear)
The state of the art industrial manufacturing process to produce shafts as counter surfaces for radial shaft seal rings is plunge grinding. This process consists of three major steps. The blank is turned to a slight diameter-oversize followed by the heat treatment and the hard-finishing by plunge grinding. The geometric surface structures of the resulting shafts in general exhibit a stochastic distribution. These surface characteristics contribute to a reliable and stable sealing functionality. And the surface and subsurface hardness generally leads to a higher wear resistance of the shaft. Motivated by economic benefits and in order to achieve a compact production process for at least ten years, turning is investigated as an alternative manufacturing process. However due to the resulting lead structure on the shaft surface and the associated risk of leakage it has not become prevalent yet. In this paper turned shafts of the metastable austenitic steel AISI 347 (1.4550, X6CrNiNb1810) are investigated as alternative material for counter surfaces of radial shaft seal rings and compared to turned shafts of carburized AISI 5115 (1.7131, 16MnCr5). In addition to surfaces dry turned at room-temperature, cryogenic turned AISI 347 counter surfaces are analyzed. By applying cryogenic cooling, the formation of deformation-induced α′-martensite in the surface layer is possible during the turning process. Endurance tests in radial shaft seal ring test rigs are performed and complemented with detailed investigations of microstructure, micro-hardness and surface topography. The results are compared to results of state of the art ground AISI 5115 shafts.
Keywords: Radial shaft seal ring; Shaft surface; Cryogenic turning; Metastable austenitic steel; Deformation-induced martensite formation

Worm Gear Drives with High Efficiency - Oehler, M; Magyar, Balázs; Sauer, B (VDI-Berichte 2255)

Calculation of the efficiency of worm gear drives - Magyar, Balázs; Sauer, B (Power Transmission Engineering)

Wellendichtsysteme - Zimmer, Detmar; Nolte, Karsten; Hütte, Jürgen

Extension of prior developed design rules (LS) - Adam, Guido; Zimmer, Detmar (ASPE - Spring topical meeting 2014)

Systematic investigations of minimum feature sizes and geometrical accuracies - Adam, Guido; Zimmer, Detmar

Design for Additive Manufacturing - Element transitions and aggregated structures - Adam, Guido; Zimmer, Detmar (CIRP Journal of Manufacturing Science and Technology)
Additive Manufacturing technologies create parts layer by layer. Thereby, lots of benefits are offered. Especially extended design freedoms provide new potentials for the design of technical parts. To make these benefits accessible to different user groups, design rules for Additive Manufacturing were developed within the project ‘‘Direct Manufacturing Design Rules’’. Therefore a process independent method was defined first. Next, design rules were developed for Laser Sintering, Laser Melting and Fused Deposition Modeling. The results were summarized in a design rule catalog and support a suitable design for Additive Manufacturing

Erweiterung des Gültigkeitsbereichs von Konstruktionsregeln beim Lasersintern - Adam, Guido

Extension of prior developed design rules for laser sintering - Adam, Guido

Data Acquisition and Signal Analysis from Measured Motor Currents for Defect Detection in Electromechanical Drive Systems - Lessmeier, Christian; Enge-Rosenblatt, Olaf; Bayer, Christian; Zimmer, Detmar (European Conference of the PHM Society 2014 (EPHM14))

Auswahl anwendungsoptimaler Antriebssysteme als Basis für die Komposition von Antriebsbaukästen - Klause, Alexander; Zimmer, Detmar (Entwerfen - Entwickeln - Erleben 2014. Beiträge zur virtuellen Produktentwicklung und Konstruktionstechnik)

Intelligent Operating Strategies for Multi-Motor Drive Systems - Strop, Malte; Hölscher, Christian; Zimmer, Detmar (OPT-i 2014. 1st International Conference on Engineering and Applied Sciences Optimization)

Intelligente Betriebsstrategien für Mehrmotorenantriebssysteme - Zimmer, Detmar; Hölscher, Christian; Strop, Malte (Newsletter der Wissenschaftlichen Gesellschaft für Produktentwicklung)

Konzeption von Antriebssystembaukästen auf der Basis von branchenspezifischen Antriebslösungen - Klause, Alexander; Zimmer, Detmar (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)

intelligent Drive Module (iDM) - Hölscher, Christian; Zimmer, Detmar

Application of Self-optimizing Systems - Hölscher, Christian; Keßler, Jan Henning; Meyer, Tobias; Rasche, Christoph; Reinold, Peter; Sextro, Walter

A comprehensive model of wear, friction and contact temperature in radial shaft seals - Frölich, D.; Magyar, Balázs; Sauer, B. (Wear)
Radial shaft seals are used in a variety of applications, where rotating shafts in steady housings have to be sealed. Typical examples are crankshafts, camshafts, differential gear or hydraulic pumps. In the operating state the elastomeric seal ring and the shaft are separated by a lubrication film of just a few micrometers. Due to shear strain and fluid friction the contact area is subject to a higher temperature than the rest of the seal ring. The stiffness of the elastomeric material is intensely influenced by this temperature and thus contact pressure, friction and wear also strongly depend on the contact temperature. In order to simulate the contact behavior of elastomer seal rings it is essential to use a comprehensive approach which takes into consideration the interaction of temperature, friction and wear. Based on this idea a macroscopic simulation model has been developed at the MEGT. It combines a finite element approach for the simulation of contact pressure at different wear states, a semi-analytical approach for the calculation of contact temperature and an empirical approach for the calculation of friction. In this paper the model setup is presented, as well as simulation and experimental results.
Keywords: Radial shaft seal ring; Contact temperature; Wear; Friction torque; Finite element simulation

Tribologische Untersuchung eines neuen Werkzeughalters zur Polierbearbeitung von keramischen Fliesen - Sousa, F.J.P.; Glawe, M; Magyar, Balázs

Numerical Investigation of the Contact of Rough Surfaces - Magyar, Balázs; Sauer, B

Calculation of the efficiency of worm gear drives - Magyar, Balázs; Sauer, B

Simulation der Hysteresereibung von Elastomeren - Magyar, Balázs; Sauer, B

Semi-Analytical Model for the Contact Temperature Calculation in Radial Shaft Seals - Frölich, D; Magyar, Balázs; Sauer, B

Theoretical Analysis of the Local Load Distribution of Rough Surfaces - Magyar, Balázs; Sauer, B

On the fatigue properties of metals manufactured by selective laser melting – The role of ductility - Leuders, Stefan; Lieneke, Tobias; Lammers, Stefan; Tröster, Thomas; Niendorf, Thomas (Journal of Materials Research)
Abstract

Design for additive manufacturing - Adam, Guido; Zimmer, Detmar

Konstruktionsregeln für additive Fertigungsverfahren - Adam, Guido; Zimmer, Detmar (Konstruktion)
Additive Fertigungsverfahren stellen Bauteile und Baugruppen aus Kunststoff- oder Metallwerkstoffen schicht¬weise, ohne formgebendes Werkzeug her. Daraus resultierende Gestaltungsmöglichkeiten schaffen einen großen Nutzen für Anwender dieser Technologie. Um diesen Nutzen einem breiten An-wenderkreis zugänglich zu machen, werden im Projekt „Direct Manufacturing Design Rules“ (DMDR) Konstruktionsregeln für Additive Fertigungsverfahren erarbeitet. Hierzu wird zunächst eine verfahrens-unabhängige Methode zur Erarbeitung der Konstruktionsregeln entwickelt. Diese ermöglicht die Erar-beitung von Konstruktionsregeln, die zunächst für die hier betrachteten Additiven Fertigungsverfahren und Werkstoffe gelten. Die Ergebnisse werden in einem Konstruktionsregelkatalog zusammengefasst.

Die Potentiale additiver Fertigung nutzen - Adam, Guido

Konstruktionsregeln für additive Fertigungsverfahren - Ausbildung, Lehre - Adam, Guido

Ökonomisch-ökologische Bewertung von elektromechanischen Antriebssystemkonzepten. Ein Werkzeug zur schnellen und wirtschaftlichen Konzipierung optimaler Antriebssysteme für spezifische Anwendungen - Zimmer, Detmar; Klause, Alexander (Newsletter der Wissenschaftlichen Gesellschaft für Produktentwicklung)

Multiobjective Optimization including Safety of Operation Applied to a Linear Drive System - Meyer, Tobias; Hölscher, Christian; Menke, Michael; Sextro, Walter; Zimmer, Detmar (PAMM - Proceedings in Applied Mathematics and Mechanics)

Energetische Optimierung eines Mehrmotorenantriebssystems für Kautschukinnenmischer - Hölscher, Christian; Michaelis, Stefanie; Strop, Malte; Zimmer, Detmar

Situationsbezogene Luftspaltoptimierung am Linearmotor eines schienengebundenen Fahrzeugs - Schmidt, Alexander

Beitrag zur Geräuschminderung an Federkraftbremsen - Wecker, Markus

AutASS - Autonome Antriebstechnik durch Sensorfusion für die intelligente, simulationsbasierte Überwachung & Steuerung von Produktionsanlagen“ Teilvorhaben: „Beanspruchungs- und Lastkollektivbestimmung“ - Lessmeier, Christian; Kürpick, Markus; Zimmer, Detmar

Tribo-Dynamical Analysis of Cylindrical Worm Gear Drives - Magyar, Balázs; Sauer, B; Horák, P (VDI Berichte 2199)

Temperaturberechnung im RWDR-Dichtkontakt - Magyar, Balázs; Frölich, D; Sauer, B

Contact Modeling of Rough Surfaces - Magyar, Balázs; Sauer, B

Elementbasierte Erarbeitung von Konstruktionsregeln für additive Fertigung - Adam, Guido; Zimmer, Detmar

Untersuchung von Bauteilschäden elektrischer Antriebsstränge im Belastungsprüfstand mittels Statorstromanalyse - Zimmer, Detmar; Lessmeier, Christian; Hameyer, Kay; Piantsop Mbo'o, Christelle; Coenen, Isabel (ant Journal - Anwendungsnahe Forschung für Antriebstechnik im Maschinenbau)

Anforderungen an Bremssysteme in der industriellen Antriebstechnik - Kriegel, Nils-Peter; Wecker, Markus; Zimmer, Detmar (VDI-Konferenz Innovative Bremstechnik)

Untersuchung von Bauteilschäden elektrischer Antriebsstränge im Belastungsprüfstand mittels Statorstromanalyse - Lessmeier, Christian; Piantsop Mbo'o, Christelle; Coenen, Isabel; Zimmer, Detmar; Hameyer, Kay

Anforderungen an Bremssysteme der industriellen Antriebstechnik - Kriegel, Nils-Peter; Zimmer, Detmar (Newsletter der Wissenschaftlichen Gesellschaft für Produktentwicklung)

Low friction Rotary Shaft Seal. Verlustleistungsreduziertes Dichtsystem - Nolte, Karsten; Zimmer, Detmar (International Sealing Conference)

Hierarchical optimization of coupled self-optimizing systems - Hölscher, Christian; Zimmer, Detmar; Keßler, Jan Henning; Kruger, Martin; Trächtler, Ansgar (IEEE International Conference on Industrial Informatics)

Entwicklung eines modularen Antriebssystems für Kautschukinnenmischer - Fiekens, Nicolas; Zimmer, Detmar; Michaelis, Stefanie; Schöppner, Volker; Hallmann, Tobias (DKT 2012. Deutsche Kautschuk Tagung)

Elektromechanische Antriebe - Zimmer, Detmar

Simulation and Experimental Analysis of Mixed Lubrication of K Type Worm Gear Drives - Magyar, Balázs; Sauer, B; Horák, P

Kontaktmodellierung von technisch rauen Oberflächen - Magyar, Balázs; Sauer, B

Tribological Investigation of K Type Worm Gear Drives - Magyar, Balázs; Sauer, B; Horák, P (Acta Polytechnica Hungarica)

Tribo-dynamische Untersuchungen von Zylinderschneckengetrieben - Magyar, Balázs

Direct Manufacturing Design Rules - Adam, Guido; Zimmer, Detmar

Steigerung der Anlagenverfügbarkeit von Antriebssystemen durch methodische und modulare Konzeption. Modulare Konzeption von als Einzelstücke oder in Kleinserien hergestellten Antriebssystemen mit großer Nennleistung - Fiekens, Nicolas; Zimmer, Detmar (VDI/VDE-Tagung mit Fachausstellung Antriebssysteme 2011. Elektrik, Mechanik und Hydraulik in der Anwendung)

DMDR Direct Manufacturing Design Rules. Erarbeiten von applikationsunabhängigen Konstruktionsregeln - Zimmer, Detmar; Adam, Guido (Rapid.Tech 2011 Fachmesse und Anwendertagung für Rapid-Technologie)

Bestimmung der Biegesteifigkeit eines Schubgliederbandes - Zimmer, Detmar; Möller, Jens (Konstruktion - Zeitschrift für Produktentwicklung und Ingenieur-Werkstoffe)

Hybrid Planning for Self-Optimization in Railbound Mechatronic Systems - Adelt, Philipp; Esau, Natascha; Hölscher, Christian; Kleinjohann, Bernd; Kleinjohann, Lisa; Krüger, Martin; Zimmer, Detmar

Component-Based Hazard Analysis for Mechatronic Systems - Priesterjahn, Claudia; Sondermann-Wölke, Christoph; Tichy, Matthias; Hölscher, Christian (14th IEEE International Symposium on Object/Component/Service-Oriented Real-Time Distributed Computing Workshops)

Experimentelle Untersuchungen zur Ermittlung der Schwingungsdämpfung von Zylinderschneckengetrieben - Magyar, Balázs; Fábián, Cs.; Sauer, B (VDI-Berichte 2164)

Dynamiksimulation von im Mischreibungsgebiet arbeitenden Schneckengetrieben - Magyar, Balázs; Sauer, B; Horák, P (VDI-Berichte 2155)

Konstruktionsregeln für additive Fertigung in Lehre und Forschung - Adam, Guido; Zimmer, Detmar (Newsletter Berliner Kreis)

Visualisierung zum technischen Review eines elektrischen Linearantriebs in der virtuellen Umgebung - Radkowski, Rafael; Hölscher, Christian; Speith, Markus; Hilus, Michael (IFF-Wissenschaftstage)

Rechnerische und experimentelle Bestimmung der Lagerkräfte eines stufenlosen Umschlingungsgetriebes - Möller, Jens

Numerical and Experimental Analysis of TEHD Lubrication of ZK Type Worm Gear Drives - Magyar, Balázs; Horák, P (VDI-Berichte 2108)

Investigation of the Lubrication of ZI Type Worm Gear Drives - Magyar, Balázs; Horák, P

Experimentelle Untersuchung der Zahnreibungszahl von Schneckengetrieben mit der Flankenform K - Magyar, Balázs; Horák, P; Sauer, B; Fábián, Cs (GÉP)

Überlegung zur Senkung des Energieeintrags bei der Compoundierung - Hallmann, Tobias; Schöppner, Volker; Fiekens, Nicolas; Zimmer, Detmar (VDI-Fachtagung Aufbereitungstechnik)

Methodische Modularisierung komplexer Produktstrukturen - Fiekens, Nicolas; Zimmer, Detmar (Konferenz Variantenmanagement im Produktentstehungsprozess im Maschinen- und Anlagenbau)

Ermittlung der Verluste von Schneckengetrieben mit ZK-Schnecke - Magyar, Balázs; Horák, P (GÉP)

Systematic analysis of the synchronization of twin screw extruders - Kriegel, Nils-Peter (International Rubber Mixing Symposium)

Approximation of Environment Models for an Air Gap Adjustment System in a Hybrid Planning Context - Adelt, Philipp; Schmidt, Alexander; Esau, Natascha; Kleinjohann, Lisa; Kleinjohann, Bernd; Rose, Mirko (MSC2008)

Interval Optimization in a Hybrid Planner Context for an Air Gap Adaptation System - Esau, Natascha; Adelt, Philipp; Schmidt, Alexander; Rose, Mirko (AISM 2008. 3rd Asia International Symposium on Mechatronics)

Holistic Conceptual Design of Self-Optimizing Systems - Gausemeier, Jürgen; Kahl, Sascha; Zimmer, Detmar; Schmidt, Alexander (AISM 2008. 3rd Asia International Symposium on Mechatronics)

Integrating dynamic track sectioning into a hybrid planning infrastructure - Schmidt, Alexander; Adelt, Philipp; Esau, Natascha (International Conference on Instrumentation, Control and Information Technology)

Determination of Active Pattern during the Conceptual Design of Self-Optimizing Systems Demonstrated by an Air Gap Adjustment System - Gausemeier, Jürgen; Podlogar, Herbert; Donoth, Jörg; Zimmer, Detmar; Schmidt, Alexander (International Conference on Systems Engineering)

Dynamic optimization of track sectioning in mechatronic systems for a hybrid planner - Schmidt, Alexander; Esau, Natascha; Adelt, Philipp; Stern, Claudius (IEEE International Conference on Mechatronics and Automation)

Development of Self-Optimizing Systems. Domain-Spanning and Domain-Specific Models Exemplified by an Air Gap Adjustment System for Autonomous Vehicles - Henkler, Stefan; Hirsch, Martin; Kahl, Sascha; Schmidt, Alexander (Computers and Information in Engineering Conference, Parts A and B)

Defining Plan Metrics for Multi-Agent Planning Within Mechatronic Systems - Klöpper, Benjamin; Romaus, Christoph; Schmidt, Alexander; Vöcking, Henner; Donoth, Jörg (Computers and Information in Engineering Conference, Parts A and B)

Using Enviromental Models Approximated by Fuzzy Identification for Hybrid Planning of Mechatronic Systems - Schmidt, Alexander; Adelt, Philipp; Esau, Natascha; Kleinjohann, Lisa; Kleinjohann, Bernd (Computers and Information in Engineering Conference, Parts A and B)

Proceedings for the conceptual design of self-optimizing mechatronic systems - Gausemeier, Jürgen; Zimmer, Detmar; Donoth, Jörg; Pook, Sebastian; Schmidt, Alexander (DESIGN 2008, International Design Conference)

A Multi-Agent Planning Problem for the Coordination of Function Modules - Klöpper, Benjamin; Romaus, Christoph; Schmidt, Alexander; Vöcking, Henner

Conceptual Design of Self-Optimizing Mechatronic Systems - Gausemeier, Jürgen; Donoth, Jörg; Pook, Sebastian; Zimmer, Detmar; Schmidt, Alexander

Geometrical modeling and investigation of the contact relations of spatial gears - Magyar, Balázs; Horák, P

Geometrische Modellierung und Untersuchung der Berührungsverhältnisse bei den Räumlichenverzahnungen - Magyar, Balázs; Horák, P (GÉP)